2019
DOI: 10.3168/jds.2018-14962
|View full text |Cite
|
Sign up to set email alerts
|

Cooling cows with sprinklers: Effects of soaker flow rate and timing on behavioral and physiological responses to heat load and production

Abstract: Spray strategies (e.g., flow rate and spray timing) may affect the surrounding microclimate and how cows use soakers, affecting cooling efficiency. Our objective was to evaluate the combined effects of spray timing (i.e., frequency, low: 3 min on, 6 min off; or high: 1.5 min on, 3 min off) and flow rates (3.3 or 4.9 L/min) on behavioral and physiological responses to heat load and production in Holstein cows managed in a freestall barn. In a 2 × 2 Latin square design, 3 cohorts of 4 pairs of cows averaging (±s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
27
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 45 publications
6
27
2
Order By: Relevance
“…Cows spent an average of 12.3 h/d lying, which is comparable to the 12.5 h/d observed from previous work conducted by our team (e.g., Chen et al, 2016;Tresoldi et al, 2019). As heat load increases, cows spend less time lying down (Cook et al, 2007;Schütz et al, 2010;Chen et al, 2016), which would prevent conductive cooling via the freestall surface.…”
Section: Effects Of Heat Abatement On Behavioral Responsesupporting
confidence: 76%
See 2 more Smart Citations
“…Cows spent an average of 12.3 h/d lying, which is comparable to the 12.5 h/d observed from previous work conducted by our team (e.g., Chen et al, 2016;Tresoldi et al, 2019). As heat load increases, cows spend less time lying down (Cook et al, 2007;Schütz et al, 2010;Chen et al, 2016), which would prevent conductive cooling via the freestall surface.…”
Section: Effects Of Heat Abatement On Behavioral Responsesupporting
confidence: 76%
“…The time spent near the feed bunk was comparable to the 7.8 h/d observed by Chen et al (2013). However, it was greater than the 5.2 to 5.8 h/d observed in other studies (DeVries et al, 2003;Tucker et al, 2006;Tresoldi et al, 2019). These differences may be a result of climate conditions or the amount of time heat abatement was offered at the feed bunk.…”
Section: Effects Of Heat Abatement On Behavioral Responsesupporting
confidence: 49%
See 1 more Smart Citation
“…Numerous studies consistently report that, as ambient temperatures increase in summer, dairy cows spend less time lying down (Shultz, 1984;Wagner-Storch et al, 2003;Cook et al, 2004Cook et al, , 2007Zähner et al, 2004;Tapkı and Şahin, 2006;Tucker et al, 2008;Schütz et al, 2010bSchütz et al, , 2020Legrand et al, 2011;Chen et al, 2013Chen et al, , 2016aMattachini et al, 2017;Tresoldi et al, 2019), regardless of provision of heat abatement (Overton et al, 2002;Legrand et al, 2011;Chen et al, 2013Chen et al, , 2016a. Both Chen et al (2016a) and Tresoldi et al (2019) found that daily lying time is reduced by 21 to 22 min for every 1°C increase in ambient temperature, within the range tested, whereas King et al (2016) report a more modest 15-min reduction for every additional 10°C. Fewer studies have examined the effects of winter weather.…”
Section: Weather and Climatementioning
confidence: 81%
“…Physical modification of the environment to reduce ambient temperature or increase heat loss from the animal body, such as shading and fans, have been previously applied for lactating buffaloes with positive results [29], and in dairy cows using mixed-flow fans [30]. However, one of the most effective methods found is spraying water over animals using sprinkler systems [31][32][33][34]. This paper proposed the implementation of Model 2 with an automated system based on an individual cow assessment combined with environmental factors obtained from an automatic meteorological station (AME) (Figure 4).…”
Section: Artificial Intelligence To Manage Heat Stress and Milk Productivitymentioning
confidence: 99%